Another Sherlock Holmes Mystery: Abdominal Pain Explained by Median Arcuate Ligament Syndrome. (March 2022) - Ortega, Andrew J.; Memon, Hadiqa; Trivedi, Bhavi; Davis, Brian; McCallum, Richard
Median arcuate ligament syndrome (MALS), also known as celiac artery compression syndrome, is a rare gastrointestinal condition with an estimated incidence of 2 per 100 000 population. Predominantly in female patients, this syndrome is characterized by the compression of the celiac artery at its origin from the aorta by the median arcuate ligament, which at the same time is entrapping the celiac plexus, causing upper abdominal pain, notably postprandial pain, as well as nausea, vomiting, food aversion, and weight loss. We present a case of abdominal pain secondary to MALS that was appropriately diagnosed after requiring narcotic medication, which responded to surgical therapy.